ACCOUNTING FOR FIXED ASSETS AND THEIR AMORTIZATION. - Grady, Paul (The Accounting Review, 1950)
The article focuses on accounting for fixed asset and their amortization. Accounting for the acquisition and construction of the fixed assets required in the production and distribution of goods and services is important to business managements and to the accounting profession. There have been changes in the past fifty years of kaleidoscopic economic and political events and social movements. Since the fixed assets and the related amortization accounts are continuing historical accounts, the present balances have obviously been affected by any changes made in accounting practice over the years resulting from changes in business conditions, in the purposes of the accounts and in mode of thought of various managements and their accounting advisors. The principal accounting points discussed regarding fixed assets and their amortization includes accounting entity, monetary basis for carrying fixed assets, cost, close relationship between tangible and intangible fixed assets and their amortization.